Legal Liability for Violations of Outsourced Workers’ Rights in Indonesia from the Perspective of Comparative Joint Liability Principles in Spain and the Philippines: Pertanggungjawaban Hukum atas Pelanggaran Hak Pekerja Outsourcing di Indonesia dalam Perspektif Perbandingan Prinsip Joint Liability di Spanyol dan Filipina - Christina, Nadya; Gunadi, Ariawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The widespread adoption of outsourcing in Indonesia aims to enhance corporate flexibility and efficiency. Specific Background: Despite comprehensive regulation under UU 13/2003, UU 6/2023, and PP 35/2021, outsourced workers frequently experience violations of fundamental rights due to unclear allocation of legal responsibilities between outsourcing providers and user companies. Knowledge Gap: Existing Indonesian regulations place full liability solely on outsourcing companies, leaving limited legal remedies when providers fail to fulfil obligations, unlike countries applying joint liability. Aims: This study analyzes Indonesia’s legal framework on outsourced workers’ rights and compares it with the joint liability principles adopted in Spain and the Philippines. Results: Findings indicate that Indonesia’s system creates structural protection gaps, while Spain and the Philippines impose solidary responsibility on both provider and user companies, ensuring stronger enforcement of wages, social security, and working conditions. Novelty: This research provides a comparative legal perspective demonstrating how joint liability can operate as an equitable mechanism for outsourced worker protection. Implications: Adoption of joint liability in Indonesia could enhance legal certainty, prevent responsibility evasion, and strengthen workers’ access to remedies, offering a policy alternative for future legislative reform. Highlights: Indonesia’s current framework places full responsibility on outsourcing providers, creating protection gaps. Spain and the Philippines strengthen worker rights through solidary (joint) liability between providers and user companies. Joint liability offers a viable reform option to enhance fairness and legal certainty for outsourced workers in Indonesia. Keywords: Outsourcing, Legal Liability, Joint Liability, Worker Protection, Comparative Labor Law